Development of trivalent DNA vaccine encapsulated in chitosan TPP nanoparticles against EV-A71 and CV-A16 - Yew, Jia Sheng * (2024)
Hand foot and mouth disease (HFMD) is a prevalent global disease commonly occurring in young children under 6 years of age. Enterovirus 71 (EV-A71) and Coxsackievirus 16 (CV-A16) have been isolated as the major causative agents for most HFMD outbreaks in the Asia Pacific region. Severe HFMD could lead to cardiopulmonary and neurological failure or death. Currently, there are no US-FDA approved HFMD vaccines or antiviral treatments available in the market. The current China FDA approved vaccine for HFMD is a monovalent inactivated vaccine targeting EV-A71 without providing protection against CV-A16. In this study, we attempt to design a trivalent DNA vaccine candidate that could be administered to confer cross protection against EV-A71 and CV-A16. Chitosan-TPP Nanoparticles encapsulation of plasmid vaccine candidate was carried out to enhance immune response and prevent degradation. The VP1, VP2 genes of EV-A71 and VP1 gene of CV-A16 were cloned into the pIRES2-AcGFP1vector to form the recombinant plasmid pIRES-VP121. Chitosan TPP nanoparticles (NPs) encapsulating the trivalent pDNA were synthesized through ionic gelation followed by in vitro characterization. In vivo immunization of 4 weeks old ICR mice was carried out to evaluate the immunologic enhancement of Chitosan Nanoparticles. The formulated chitosan TPP (CS-TPP-NPs (pIRES-VP121)) were highly monodispersed with an average size of ~200nm. Chitosan TPP NPs encapsulating the pDNA showed >70% encapsulation efficiency and good cellular uptake in mice macrophage cells were observed. The plasmid DNA vaccine was protected from DNase I digestion by chitosan TPP NPs. In vivo immunization studies demonstrated enhanced immunogenic responses by CS-TPP-NPs (pIRES-VP121) due to self adjuvanting properties of chitosan nanoparticles. Mice administered with CS-TPP NPs (pIRES-VP121) intramuscularly were observed to have the highest IFN-γ response (~15-fold increment). Sera from mice immunized with the naked pDNA and CS-TPP-NPs (pIRES-VP121) demonstrated good viral clearance against wild-type EV-A71 and CV-A16 in RD cells. Unfortunately, murine sera administered with naked pDNA and CS-TPP-NPs (pIRES-VP121) showed reduced ability to neutralize mouse adapted virus (MAV) strains of EV-A71 and CV-A16. CS-TPP-NPs (pIRES-VP121) could serve as a prototype for future development of multivalent HFMD DNA vaccine candidates.